One-pot transformation of Me3Si-/Ph2P(O)-protected ethynes to unsymmetrical arylethynes. (1st June 2018) - Peng, Li-Fen; Lei, Jia-Ying; Wu, Li; Tang, Zi-Long; Luo, Zhi-Peng; Jiao, Yin-Chun; Xu, Xin-Hua
Me3Si-/Ph2P(O)-protected ethynes were successfully transformed to unsymmetrical arylethynes via a one-pot Ph2P(O)-deprotection/[Pd(dppf)Cl2]-catalysed coupling and one-pot Me3Si-deprotection/Sonogashira coupling under mild conditions and in high yield. Unsymmetrical phenylethynes, unsymmetrical extended phenylene ethynylenes and unsymmetrical anthrylethynes were successfully synthesised in good to excellent yields.